2005
DOI: 10.1021/ic050895m
|View full text |Cite
|
Sign up to set email alerts
|

Camouflaged Carborane Amphiphiles:  Synthesis and Self-Assembly

Abstract: A series of amphiphilic amine hydrochloride salts of B-polymethylated (camouflaged) (aminoalkyl)- and bis(aminoalkyl)carboranes have been designed and synthesized in high yield for the purpose of constructing novel carborane-based nanomaterials. Due to the distinct separation of the hydrophobic and hydrophilic regions within each salt, the mono- and disubstituted amphiphiles spontaneously self-assembled upon sonication into rod-shape micro/nanostructures in aqueous solutions. The effects of concentration, meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…One of the earliest basic studies on self-assembly in 2001 and 2005 were conducted by Hawthorne and co-workers on ortho-, meta-and para-carboranes mono-and di-C-substituted with aminoalkyl chains of varying lengths, resulting in amphiphilic structures which spontaneously formed self-assembled rod-shaped micro-and nanostructures upon sonication in aqueous solutions. [40,41] TEM and optical microscopy showed that the orientation of the side chains (ortho, meta, or para, affect the dipole moment, little effect), the side-chain length (little effect), the counterion identity (varying effect), the number of the side chains attached, and the hydrophobicity (high impact) have an effect on the self-assembly. These conclusions run like a golden thread through the whole story of influencing parameters on self-assembly of carboranes.…”
Section: Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the earliest basic studies on self-assembly in 2001 and 2005 were conducted by Hawthorne and co-workers on ortho-, meta-and para-carboranes mono-and di-C-substituted with aminoalkyl chains of varying lengths, resulting in amphiphilic structures which spontaneously formed self-assembled rod-shaped micro-and nanostructures upon sonication in aqueous solutions. [40,41] TEM and optical microscopy showed that the orientation of the side chains (ortho, meta, or para, affect the dipole moment, little effect), the side-chain length (little effect), the counterion identity (varying effect), the number of the side chains attached, and the hydrophobicity (high impact) have an effect on the self-assembly. These conclusions run like a golden thread through the whole story of influencing parameters on self-assembly of carboranes.…”
Section: Self-assemblymentioning
confidence: 99%
“…[9,[35][36][37][38][39] In contrast, only a few reports exist which suggest that also non-ionic icosahedral (metalla)carboranes show a tendency to aggregate into nano-and micro-entities in aqueous solutions. [40][41][42][43][44][45][46] However, investigations which translate the physicochemical self-assembling behaviour to the biological concept of colloidal drug aggregates are missing, except our most recent work. [47] Thus, we have shown that neutral boron cluster compounds spontaneously aggregate in buffered solutions and/or in cell culture media.…”
Section: Introductionmentioning
confidence: 99%
“…The nido-[MgMCHESPz]K 8 (16) complex is soluble in acetone, water, methanol, and mixtures of them. It shows a well-resolved UV-vis spectrum in acetone, with the most intense band, the Q band, peaking at 668 nm.…”
Section: Synthesis and Characterization Of Water-soluble Carboranylpomentioning
confidence: 99%
“…In the past 15 years, several BNCT (Boron Neutron Capture Therapy) agents [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] have been proposed, including boronated nucleosides [5][6][7][8][9], amino acids and peptides [10,11], phospholipids [12], monoclonal antibodies, liposomes [13][14][15], closomers [16,17], and dendrimers [18,19]. Tetrapyrrolic macrocycles, a vast class of biologically relevant compounds often employed as sensitizers in anti-cancer photomedical treatments (including photodynamic therapy (PDT) [20][21][22][23][24] and photothermal therapy (PTT) [25][26][27][28]), have also been derivatized with boron-containing functions for possible use in BNCT [20,[29][30][31]…”
Section: Introductionmentioning
confidence: 99%
“…Several BNCT agents have been proposed so far, including boronated nucleosides [6,7], amino acids and peptides [8,9], phospholipids and liposomes [10][11][12][13], monoclonal antibodies, closomers [14,15], and dendrimers [16]. Due to their selectivity of accumulation in tumor over many normal tissues, porphyrins and phthalocyanines have also been proposed as boron carriers to target tumoral tissues in BNCT treatment, and indeed a number of papers reported the synthesis of carboranyl-porphyrins [17][18][19][20][21][22] and phthalocyanines [23,24] as model to develop novel radiosensitizers.…”
Section: Introductionmentioning
confidence: 99%